Obesity, gestational diabetes and macrosomia are associated with increasing rates of early‐term induction of labour at The Canberra Hospital. (2nd May 2018) - McGuane, Jonathan T.; Grlj, Lori; Peek, Michael J.
Abstract : Background: Early‐term delivery is an important cause of short‐term neonatal morbidity and associated high healthcare costs, with possible additional long‐term developmental ramifications. As a form of 'iatrogenic' delivery, induction of labour (IOL) is a potentially modifiable contributor to this burden. Aims: To determine patterns of, and primary indication for, early‐term IOL, as well as temporal trends in this primary indication and differences from other modes of delivery with respect to maternal factors and maternal/neonatal outcomes. Materials and Methods: The Canberra Hospital births database (2012–2016) was queried; patients who underwent IOL were included in the analysis. Results: Total deliveries and the proportion of early‐term IOL procedures rose markedly over the time period. Gestational diabetes mellitus (GDM) was the most frequent and an increasing main indication for IOL. GDM was associated with significantly higher body mass index, an increased proportion of obesity, and a greater incidence of labour complications related to macrosomia. Birthweight of neonates of diabetic mothers was significantly higher, which was associated with decreased rates of admission to the special care nursery/neonatal intensive care unit (SCN/NICU) compared to all other babies. GDM increased relative risk of early‐term IOL in obese women by 1.8 times. Conclusions: The burden of GDM and early‐term IOL have increased at The Canberra Hospital although adverse short‐term neonatal outcomes have not, possibly suggesting appropriate management of these patients. Nonetheless, effort should be made to identify patients who can safely continue pregnancy to full term, given the higher proportion of SCN/NICU admissions among early‐term neonates.